PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DENGAN METODE OBSERVASI UNTUK MENINGKATKAN HASIL BELAJAR PADA MATAKULIAH EKOLOGI DASAR - Hanik, Nur Rokhimah; Harsono, Sri; Nugroho, Anwari Adi (Jurnal Pendidikan Matematika dan IPA, 2018)
ABSTRACT Implementation of learning at the university level is expected to be conducted interactively and motivate students to participate actively in learning activities. But the reality in learning, still found learning problems about the low learning activities and student learning outcomes. While as an educator, lecturers should be able to know the problems in the learning process or lectures as an effort to improve the quality of learning. Solution to overcome the problem is by giving learning with Contextual Teaching and Learning approach (CTL) through observation method applied in Basic Ecology subject.The purpose of this research is to improve student achievement in Basic Ecology subject through learning with CTL approach and observation method. Expectations from the results of this study is as an information or input that the strategy and learning model with the method of observation can overcome the lack of activity and low student learning outcomes caused by the dominance of female students and the diversity of high school students so that the classroom climate is often noisy and reduced concentration at the time of learning. This research is experimental research, with one class of experiment of Biology student of FKIP Univet Bantara Sukoharjo second semester of class of 2016/2017 taking Basic Ecology subject. The data were collected using observation and test sheets. Technique of data analysis using T test analysis. From the analysis with T test Paired sample for two groups of dependent or pairs on pretest and postes data obtained Asymp results. Sig (2 -tailled) below 0.05 is 0.00 then Ho is rejected. This means that there are significant differences in learning outcomes before (pretest) and after CTL learning with the method of Observation (postes) in Basic Ecology subject especially on the subject matter of Population and Bird Diversity. Thus, it can be concluded that learning CTL with Observation method can improve student achievement in Basic Ecology subject especially material Population or bird diversity. Keywords: CTL approach, Observation method, Basic Ecology course, Learning  Achievement